Coexistence of nutritional problems in children 6-9 years of age, state schools in Matucana, Santa Eulalia and Lima - Pajuelo Ramírez, Jaime (2001)
Objective: To determine the coexistence of nutritional problems in public school children 6 to 9 years of age. Material and Methods: In 241 children of Matucana, Santa Eulalia and Lima public schools the body mass index (BMI) was calculated. Must et al. classification was used for nutritional diagnosis in order to respectively define deficient, low weight, normal weight, overweight and obesity. Chronic malnutrition was determined using the National Center for Health Statistics (NCSH) and anemia by less than 12 g/dL hemoglobin, adding 0,4 g/dL for each 1000 meters above sea level. Results: Children with chronic malnutrition, overweight, obesity and nutritional anemia represented 22,4, 14,1, 10,0 and 69,3% of the population studied. From those with chronic malnutrition 11,1, 9,3 and 66,7% showed overweight, obesity and anemia; and from the anemic children, 16,8 and 12,6% showed overweight and obesity. We found that 2,1% of children had chronic malnutrition, overweight and anemia and a similar percentage had chronic malnutrition, obesity and anemia. Conclusion: The presence of two or even three nutritional diseases in the same child merit the implementation of related political strategies.